Study on the jurisdiction on licensing body with reference to Trade Description Act 2011 / Md Rasyid Ridha Johdi … [et al.] - Johdi, Md Rasyid Ridha; Mohd Rozman, Mohid Roezamir; Bahauddin, Haniza; Ab Malek, Siti Noor Harlina (Faculty of Law, 2012)
The issue of halal certificate authenticity was not new for public at large. Muslim consumers are in confusion in choosing foods or food products since they are marked with various halal symbols, labels or logos affixed by manufacturers on their food packaging. To eliminate the confusion among Muslim consumers, Malaysia Department of Islamic Development (JAKIM) had introduced a Malaysian Halal logo in 2007 to be used in uniform by all manufacturers or premises provided that manufacturers must apply Halal Certificate from JAKIM or States Islamic Religious Departments (JAIN) or States Islamic Religious Council (MAIN). This policy did not prevent anyone to use expression of halal in any manner since the law permit its use in 1975. However, in the most recent development, JAKIM, MAIN and JAIN are recognized as the component of competent authorised bodies in Malaysia to issue the certificate when Trade Description Act 2011 came into force simultaneously and two new Orders namely the Trade Descriptions (Definition of Halal) Order 2011, Trade Descriptions (Certification and Marking of Halal) Order 2011 and a Regulations namely the Trade Descriptions (Certification and marking of Halal fees) Regulations 2011. This research is done to analyse the powers of JAKIM, MAIN and JAIN under the IDA 2011 as the component of competent authorised bodies in Malaysia to monitor and control the application of Halal Certificate by the food premises and manufacturers as well as the enforcement practise of JAKIM in monitoring and controlling the issuance of Halal Certificate under ID A 2011. Besides that this research will also highlight suggestions an appropriate reformation to the existing legal framework on the authoritative bodies to issue and monitor the issuance of Halal Certificate.